Distributed control of battery energy storage systems in distribution networks for voltage regulation at transmission–distribution network interconnection points. (February 2022) - Zhao, Tianqiao; Parisio, Alessandra; Milanović, Jovica V.
Abstract: This paper describes a control framework that enables distributed battery energy storage systems (BESS) connected to distribution networks (DNs) to track voltage setpoints requested by the transmission system operator (TSO) at specific interconnection points in an optimal and coordinated manner. The control design is based on an optimisation problem whose objective is to minimise the real-time voltage-tracking mismatch while satisfying local physical network constraints. A novel agent-based control scheme adopting an online convex optimisation (OCO) framework is developed and solved in a distributed fashion to guarantee the solution's scalability and the service provision within the required time. The BESS agents under the proposed control framework automatically adapt to the time-varying network conditions so as to track the required voltage setpoints whilst fulfilling the technical operating requirements of the local network. The designed OCO-based framework addresses the existing conflict between the accuracy and optimality of the solution and the communication and computational efficiency. The convergence to the optimal solution is demonstrated. Several case studies are performed to corroborate the analytical results and assess the performance of the proposed approach.